2021
DOI: 10.7150/thno.56482
|View full text |Cite
|
Sign up to set email alerts
|

Recent strategies for nano-based PTT combined with immunotherapy: from a biomaterial point of view

Abstract: Cancer has been a great threat to humans for decades. Due to the limitations of monotherapy, combinational therapies such as photothermal therapy (PTT) and immunotherapy have gained increasing attention with expectation to overcome the shortfalls of each other and obtain satisfactory therapeutic outcomes. PTT can inhibit primary tumors by thermal ablation but usually fails to achieve complete eradication and cannot prevent metastasis and recurrence. Meanwhile, the efficacy of immunotherapy is usually attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 116 publications
0
79
0
Order By: Relevance
“…As expected, the apoptosis ratio of cells treated by MDPMH under laser irradiation was higher than that of other groups, which could probably be attributed to the effect of PTT. Previous studies had confirmed that PTT could further enhance the permeability of the tumor cell membrane and thus improve the internalization of nanoparticles ( Liu et al, 2019 ; Huang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 92%
“…As expected, the apoptosis ratio of cells treated by MDPMH under laser irradiation was higher than that of other groups, which could probably be attributed to the effect of PTT. Previous studies had confirmed that PTT could further enhance the permeability of the tumor cell membrane and thus improve the internalization of nanoparticles ( Liu et al, 2019 ; Huang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 92%
“…Cancer treatment using hydrogels is being attempted because they can effectively supply drugs. In a recent study, immunostimulatory molecules or immune checkpoint inhibitors were incorporated into hydrogels and showed preventive effects against metastatic cancer [42][43][44][45] . However, when applying the hydrogel, the rst transplanted tumor was surgically removed, and the hydrogel was attached to the surgical site, which effectively prevented second-challenged metastatic cancer growth 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Common photothermal agents include inorganic photothermal agents such as gold nanomaterials and carbon-based materials and organic photothermal agents such as ICG and IR780. 175,176…”
Section: Artificial Bionic Exosomes For Breast Cancer Therapymentioning
confidence: 99%
“…Common photothermal agents include inorganic photothermal agents such as gold nanomaterials and carbon-based materials and organic photothermal agents such as ICG and IR780. 175,176 The combined therapeutic strategy of exosome-mimetic nanoparticles with chemotherapy and photothermal therapy represent a new approach to antitumor therapy. Tian et al constructed porous silica nanoparticles (E-MSNs) camouflaged by tumor cellderived exosomes (ID@E-MSNs) coloaded with ICG and DOX to achieve the synergistic treatment of breast cancer with chemotherapy and photothermal therapy.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%